STRUCTURAL PHASE TRANSITIONS AND MIXING BEHAVIOUR OF THE BA-ALUMINATE (BAAL2O4)-SR-ALUMINATE (SRAL2O4) SOLID SOLUTION - Rodehorst U.; Carpenter M.A.; Marion S.; Henderson C.M.B. (My University, 2003)
Phase transitions in the BaAl2O4-SrAl2O4 solid solution have been analysed as a function of temperature and composition using infrared (IR) powder absorption spectroscopy. The improper ferroelectric phase transition P6322 P63 (2A superstructure) in the BaAl2O4 end-member can be detected through a change in slope of the wavenumbers of hard modes at ~450 K. A change in line widths at ~520 K appears to correlate with the development of diffuse intensity in a* - b* planes of electron diffraction patterns reported elsewhere in the literature. The same shift in wavenumber of hard modes is not observed in spectra from samples with compositions corresponding to 60, 80 and 90% of BaAl2O4 component, but a change in line widths at ~500 K has been tentatively explained in terms of a different phase transition, from a P6322 parent structure to a P63 (√3A superstructure) product. Strain analysis of published high-temperature lattice parameter data suggests that the hexagonal → monoclinic transition in Sr-rich members of the solid solution may consist of two discrete transitions, and a sequence P6322 → C →2 P21 is suggested. The second transition could be related to instabilities in the hexagonal solid solution. Autocorrelation analysis of the IR spectra reveals a large positive deviation from linear behaviour across the solid solution, which is interpreted in terms of microscopic strain effects. These microscopic strains are probably responsible for the different transformation behaviour shown by samples with different compositions across the solid solution.
Keywords: Ba-Aluminate; Sr-Aluminate